Estudo do perfil químico de queijos tipo mozarela em diferentes condições de refrigeração por RMN - (:unkn) unknown (Universidade Federal de Goiás, 2015)
This study objectives to evaluate the effect of an inappropriate night cooling condition, it is practiced by some shops with processed mozzarella cheese and conventional mozzarella chemical profiles, using nuclear magnetic resonance technique (NMR). The simulation of inappropriate cooling was performed using a Styrofoam box with ice, not covered, and leaving the system to reach thermal equilibrium with the ambient temperature during the night. To make studies with processed mozzarella cheese was acquired two packages of the same batch, at local shops. Subjecting the spectral data, coming from the analysis made with HR-MAS, in the chemometric treatment was observed a tendency of discrimination in the samples exposed to different cooling conditions, and signals concerning lactose and some of fatty acids had greater influence in the observed separation. For the mozzarella cheese, in addition to NMR studies, it was also performed physical and chemical characteristics studies. For these studies, it has been acquired twenty-two trays containing sliced cheese, in the local market, which were divided into two sets with eleven trays each. Samples were analyzed in nature, using HR-MAS probe, and the crude extract using TBI probe. The identification of metabolites was done from the HSQC experiments, J-resolved and NMR ¹H, the last one being also used in the relative quantification of twelve metabolites. For the mozzarella cheese maintained under improper cooling conditions, there was a reduction in the galactose content and an increasing of amino acids and organic acids contents. The physicochemical analysis of pH, saturated fat and protein showed no significant differences that could be correlated with the different conditions of sample cooling. Finally, it has been concluded that NMR technique and chemometric tools are promising in identify the cheese samples submitted to different cooling conditions that has been studied, which could not be done using the physical and chemical parameters commonly used in cheese quality analysis.
Study of mozzarella cheese chemical profile in different cooling conditions by NMR
Keywords: Refrigeração de alimentos; Queijo mozarela; RMN; HR-MAS; PCA; Food colling; Mozzarella cheese; NMR; HR-MAS; PCA; CIENCIAS EXATAS E DA TERRA::QUIMICA